Genetic variants associated with female reproductive ageing – potential markers for assessing ovarian function and ovarian stimulation outcome. Issue 2 (August 2015) - Laisk-Podar, Triin; Kaart, Tanel; Peters, Maire; Salumets, Andres
Abstract This study searched for genetic markers of ovarian function, ovarian stimulation and IVF treatment outcome among genetic variants related to female reproductive ageing. It included 471 treatment cycles from 306 women undergoing IVF treatment. Genotypes for 36 single nucleotide polymorphisms (SNPs) were evaluated for their association with early follicular phase parameters together with ovarian stimulation and IVF outcome parameters. Results show that genetic variation related to menopause timing also affects ovarian function, as several selected genetic markers were associated with studied traits. For example, rs2153157 (SYCP2L) was associated with amount of recombinant FSH (rFSH) necessary for obtaining one oocyte (P = 0.049) and the chances of biochemical and clinical pregnancy (P = 0.024 and P = 0.011, respectively), while rs4886238 (TDRD3) showed association with both the number of punctured ovarian follicles and oocytes obtained (P = 0.008 and P = 0.037, respectively). Furthermore, FSHB polymorphisms influence early follicular phase FSH concentrations and IVF treatment outcome, whereas SNPs in FSHR affect early antral follicle count and follicle numbers obtained during ovarian stimulation. This study suggests that genetic markers of female reproductive ageing are potential new biomarker candidates that could be considered in clinical ovarian reserve and function assessment in assisted conception.